2020
DOI: 10.1111/jpi.12705
|View full text |Cite
|
Sign up to set email alerts
|

Circadian photoperiod alters TREK‐1 channel function and expression in dorsal raphe serotonergic neurons via melatonin receptor 1 signaling

Abstract: Seasonal day length has been linked to the prevalence of mood disorders, and however, the mechanisms underlying this relationship remain unknown. Previous work in our laboratory has shown that developmental exposure to seasonal photoperiods has enduring effects on the activity of mouse dorsal raphe serotonergic neurons, their intrinsic electrical properties, as well as on depression and anxiety‐related behaviors. Here we focus on the possible ionic mechanisms that underlie the observed programming of the elect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…53,54 On another level, melatonin has been showed to play a role in the photoperiod-dependent regulation of serotonin neurotransmission by the dorsal raphe nucleus, which could impact locomotor activity and mood in response to seasonal variations. 55,56 Taken together, these studies suggest that both melatonin and ipRGCs changes could take part in the modulation of the SCN activity/locomotor activity to photoperiod variation. Besides, the idea that ipRGCs could take part in seasonal adaptation has also been mentioned in a recent review.…”
Section: Discussionmentioning
confidence: 77%
“…53,54 On another level, melatonin has been showed to play a role in the photoperiod-dependent regulation of serotonin neurotransmission by the dorsal raphe nucleus, which could impact locomotor activity and mood in response to seasonal variations. 55,56 Taken together, these studies suggest that both melatonin and ipRGCs changes could take part in the modulation of the SCN activity/locomotor activity to photoperiod variation. Besides, the idea that ipRGCs could take part in seasonal adaptation has also been mentioned in a recent review.…”
Section: Discussionmentioning
confidence: 77%
“…Recent studies suggest that MT1 receptors are primarily associated with biological circadian rhythms. For instance, Giannoni-Guzmán et al ( 46 ) found that a prolonged photoperiod resulted in decreased co-expression levels of Tph2 and Pet-1 in 5-HT neurons, and this modulatory effect of the photoperiod on TREK-1 was lost in MT1 knockout mice. Li reported that melatonin reduces the expression of Nox2 and Nox4, thereby decreasing ROS levels and attenuating the inflammatory response in mice with ischemic stroke through the activation of MT2 receptors ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…Knockout also increased risk of epileptic seizures triggered by kainite or pentylenetetrazol; the mutant animals showed increased morbidity as well as increased spike amplitude and frequency, based on electroencephalography [56]. Administering spadin to mice did not reduce infarct size following focal ischemia or alleviate kainate-induced seizures [63] TREK-1 in serotonergic neurons of the dorsal raphe has recently been implicated in the circadian photoperiod [64]. Longer photoperiods may reduce TREK-1 function, since pharmacological inhibition of TREK-1 significantly increased spike frequency in animals exposed to short or equinox photoperiods but not in animals exposed to long photoperiods, which expressed lower levels of the channel [64].…”
Section: Treksmentioning
confidence: 99%